Multi-Criteria Analysis of Strategic Synergy Relationships Between a Medium-Sized Port and Its Macro-Environment [Análisis Multi-Criterio de Las Relaciones Sinérgicas Estratégicas Entre Un Puerto Mediano y Su Macro-Entorno] - Palominos-Villavicencio, F; Duran-San Martin, C (Institute of Electrical and Electronics Engineers Inc., 2016)
In this work a medium-sized port is analysed, which acts as a mixed network, interacting with private companies, trade associations, social groups and components of the State. Each public and private actor declares strategic phrases and rubrics in his/her mission, they can relate to the political, economic, social, technological and environmental multi-criteria macro-environment classification (PESTA). It can be seen that two port actors manage to engage in a synergic manner when they have a common strategic approach. In this research, a Multi-criteria Strategic Matrix (MSM) has been designed to display if each actor complies with one or more criteria of the macro-environment; then, the MSM is analysed and the specific/relative weight of each criteria is estimated, in addition to the possible combinations of strategic synergy generated in the port mixed network. Then, by using arrays of contingency and the Test Chi-square, any dependencies between criteria of the macro-environment are studied. © 2016 IEEE.